Respuesta :

The correct answer is:  [A]:  " f ⁻¹(x)  =  x + 2 " .
______________________________________________________
Explanation:
______________________________________________________
Given the function:
______________________________________________________

" f(x) = x − 2 " ;  find the "inverse function" ; 
______________________________________________________
 Write as:  " y = x 
− 2 " .
______________________________________________________
Replace the "y" with "x" ;  and the "x" with "y" ; and rewrite:
______________________________________________________
      " x  =  y 
− 2 " ; 
______________________________________________________
      Now, solve for "y" ; and isolate "y" as a single variable, on the 
"left-hand side" of the equation:
______________________________________________________
 
↔ " y − 2 = x " ; 

Now, add "2" to each side of the equation; 
  to isolate "y" on one side of the equation:

→  y − 2 + 2 = x + 2 ; 

→  y = x + 2 ; 

Now, replace the "y" ;  with:  " f ⁻¹(x) " ; and rewrite:
_______________________________________________________
 →   " f ⁻¹(x)  =  x + 2 " ;   

 →  which is:  Answer chioice:  [A]:  " f ⁻¹(x)  =  x + 2 " .
_______________________________________________________